2020
DOI: 10.3390/min10080681
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Agent–Mineral Interactions in the Reverse Flotation of Iron Ore: A Brief Review

Abstract: Froth flotation has been widely used in upgrading iron ores. Iron ore flotation can be performed in two technical routes: direct flotation of iron oxides and reverse flotation of gangue minerals with depression of iron oxides. Nowadays, reverse flotation is the most commonly used route in iron ore flotation. This review is focused on the reverse flotation of iron ores, consisting of reverse cationic flotation and reverse anionic flotation. It covers different types of collecting agents used in reverse iron ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 92 publications
2
14
0
Order By: Relevance
“…The zeta potential measurement results of pure minerals as a function of pH indicated (Figures 5-7) that the point of zero charges (pzc) of pure biotite, phlogopite, and quartz occurred around pH 2. Similar results were reported in other investigations (Table 2) [10,13,24,37,[44][45][46][47][48][49][50]. EDA solution (30 mg/dm 3 ) exhibited a positive charge over a wide pH range (Figures 5-7) which is associated with its cationic active species, e.g., aminium ion, RNH3+, and dimerization of aminium ions: (RNH3)2+.…”
Section: Residual Surface Tensionsupporting
confidence: 89%
“…The zeta potential measurement results of pure minerals as a function of pH indicated (Figures 5-7) that the point of zero charges (pzc) of pure biotite, phlogopite, and quartz occurred around pH 2. Similar results were reported in other investigations (Table 2) [10,13,24,37,[44][45][46][47][48][49][50]. EDA solution (30 mg/dm 3 ) exhibited a positive charge over a wide pH range (Figures 5-7) which is associated with its cationic active species, e.g., aminium ion, RNH3+, and dimerization of aminium ions: (RNH3)2+.…”
Section: Residual Surface Tensionsupporting
confidence: 89%
“…Anionic collectors' adsorption mechanisms such as sodium oleate onto apatite and hematite surfaces were widely reported as chemical adsorption. [46,47] Negatively shifted surface charge of these minerals confirms such an interaction.…”
Section: Zeta Potential Resultsmentioning
confidence: 66%
“…Based on the fact that CaO exists in the chemical structure of SCS, there is a strong possibility of adsorption of dissolved Ca cations (Ca 2+ and Ca(OH) + forms) on the quartz surface. [47,48] Thus, the noticeable changes in the quartz functional group (900-1200 cm −1 ) can also be attributed to the interaction of calcium ions with the quartz's surface, which requires further investigation with more detailed analyses.…”
Section: Quartzmentioning
confidence: 99%
“…Cationic amine species adsorb on the quartz surface by an electrostatic attraction mechanism and immobilization by formation of hemimicelles as proposed by Fuerstenau and Palmer (1975) and still presently accepted (Baltar, 2021). Studies by Zhang and Somasundaran (2006), Huang et al (2014) and Fan et al (2020) reported that increasing in collector concentration possibly causes the formation of a complete bilayer resulting in a surfactant concentration close to or equal to the critical hemimicelle concentration (CHC), thus reversal in the charge of the mineral surface occurs, rendering it hydrophilic again and consequently decreasing the mineral floatability. This effect was not observed for ethermonoamine in the evaluated concentrations.…”
Section: Effect Of Etheramines and Their Mixture In Depressant Absencementioning
confidence: 99%